Crucial Triad in Pulp-Dentin Complex Regeneration: Dental Stem Cells, Scaffolds, and Signaling Molecules - Ferry Sandra; Andri Sutanto; Widya Wulandari; Reynaldo Lambertus; Maria Celinna; Nurrani Mustika Dewi; Solachuddin Jauhari Arief Ichwan (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Pulp damage can lead to dentinogenesis impairment, irreversible pulpitis, or pulp necrosis. Despite being the most used endodontic procedure to treat damaged pulp, root canal therapy only results in nonvital teeth which are prone to fractures and secondary infection. Pulp-dentin regeneration has a potential to regenerate structure similar to normal pulp-dentin complex, and can be achieved by combining dental stem cells, scaffold, and signaling molecules. This article reviews the role of various types of dental stem cells, scaffolds, signaling molecules, and their combinations in regenerating pulp-dentin complex.CONTENT: Dental pulp stem cell (DPSC), stem cell from human exfoliated deciduous teeth (SHED), and dental follicle stem cell (DFSC) were reported to regenerate pulp-dentin complex in situ. SHED might be more promising than DPSCs and DFSCs for regenerating pulp-dentin complex, since SHED have a higher proliferation potential and higher expression levels of signaling molecules. Scaffolds have characteristics resembling extracellular matrix, thus providing a suitable microenvironment for transplanted dental stem cells. To accelerate the regeneration process, exogenous signaling molecules are often delivered together with dental stem cells. Scaffolds and signaling molecules have different regenerative potential, including induction of cell proliferation and migration, formation of pulp- and/or dentin-like tissue, as well as angiogenesis and neurogenesis promotion.SUMMARY: Combinations of dental stem cells, scaffold, and signaling molecules are important to achieve the functional pulp-dentin complex formation. Current trends and future directions on regenerative endodontics should be explored. The right combination of dental stem cells, scaffold, and signaling molecules could be determined based on the patients’ characteristics. Incomplete pulp-dentin regeneration could be overcome by applying dental stem cells, scaffold, and/or signaling molecules in multiple visits.KEYWORDS: pulp-dentin regeneration, regenerative endodontics, dental stem cells, scaffold, signaling molecules